CO2 room-temperature sensing material based on amino-functionalized MOF (Metal Organic Framework) material as well as preparation method and characterization thereof

By performing amino functionalization of MOF materials, the existing CO2 detection methods are solved, and high sensitivity and high selectivity CO2 detection is achieved at room temperature, which is suitable for large-scale production and application.

CN119320500APending Publication Date: 2025-01-17BEIJING FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411439329.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing CO2 detection methods are cost-effective, large in size, high in power consumption and are susceptible to electromagnetic interference, and it is difficult to achieve high sensitivity and selectivity CO2 monitoring at room temperature.

Method used

By aminofunctioning the metal-organic framework materials (MOFs), adjusting the mass ratio of metal to ligand, high sensitivity and high selectivity CO2 sensing materials were prepared, and scanning electron microscopy, X-ray diffraction, specific surface area and Characterization and analysis were performed by infrared spectroscopy and other technologies to optimize the degree of amino functionalization to improve CO2 adsorption performance.

Benefits of technology

It realizes high sensitivity and high selectivity CO2 detection under low energy consumption conditions, significantly improving the adsorption capacity and selectivity of MOF materials to CO2, and is suitable for large-scale production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320500A_ABST
    Figure CN119320500A_ABST
Patent Text Reader

Abstract

The invention relates to a CO2 room-temperature sensing material based on an amino-functionalized MOF material and a preparation method of the CO2 room-temperature sensing material. In order to sensitively monitor the content of CO2 under a room temperature condition, MIL-68 (In) and MIL-68 (In)-NH2 materials are synthesized, and the specific surface area and porosity of the materials can be effectively improved through amino functionalization, so that the CO2 adsorption capacity of the materials is enhanced. When the mass ratio of the prepared MIL-68 (In)-NH2 is 1: 0.75, the prepared MIL-68 (In)-NH2 shows excellent adsorption performance and sensing sensitivity to CO2, and is suitable for CO2 monitoring in various environments.
Need to check novelty before this filing date? Find Prior Art

Description

1. Technical Field

[0001] The present invention relates to environmental monitoring and sensing material technology, in particular to improving the room temperature sensitivity to carbon dioxide (CO2) by amino functionalization of Metal-Organic Framework (MOF), and constructing a high-performance CO2 room temperature sensing material based on this. 2. Background Technology

[0002] With the development of industry and the increase of energy consumption, the concentration of CO2 in the environment continues to rise, which not only aggravates the greenhouse effect, but also has serious impacts on air quality, human health and production safety. Therefore, it is of great practical significance to develop a sensing material that can sensitively and accurately monitor the concentration of CO2 at room temperature.

[0003] Traditional CO2 detection methods include fluorescence, gas chromatography, infrared spectroscopy, photoacoustic spectroscopy, and Severinghaus-type electrodes. Although these methods have high selectivity and gas sensitivity, they are usually costly, bulky, power-hungry, and susceptible to electromagnetic interference. Therefore, in recent years, the demand for lightweight, compact, low-power, and low-cost CO2 sensing materials has continued to increase. Common gas sensing materials include metal oxide semiconductors, polymers, and MOFs. These materials are effective in detecting H2, NH3, and NO x , CO2, volatile organic compounds (VOCs) and other fields. At the same time, CO2 can be converted and utilized through adsorption collection, and in these processes, the CO2 concentration can be accurately detected to achieve the purpose of accurately calculating the output of the conversion product. In particular, CO2 gas sensing at room temperature, achieving accurate sensing of CO2 while achieving low emissions and low energy consumption, has become a research hotspot for CO2 gas sensing materials.

[0004] MOFs are a new type of porous material, which is composed of transition metal ions or metal clusters bridged by organic ligands to generate ordered micro / mesopores and secondary structures, and has various physical and chemical properties. Compared with traditional porous materials, MOFs have more pore volume, higher specific surface area and open metal sites (OMS), showing unique advantages in the adsorption and separation of CO2. The structure of MOFs materials is easy to adjust, so there are many types. The following are the common types, MILs series, HKUST-1 series, ZIFs series, UIO series and IRMOF series. The following lists the more typical MILs series material structures. A series of functional modifications, including –NH2, –Br and –NO2, were performed on the MIL-68 (In) material to improve the porosity characteristics of the original material. Among them, the amino group is a basic group that can effectively adsorb the acidic gas CO2. And because the nitrogen atom on the amino group has a lone pair of electrons, it has a strong affinity with the CO2 gas molecule. Therefore, by amino-modifying the metal-organic framework material, the material's adsorption performance for CO2 can be significantly improved.

[0005] Based on the above considerations, the present invention studies amino-functionalized MOFs gas sensing materials to detect CO2 gas at room temperature, which can be applied to different fields such as air quality monitoring, fire detection, greenhouse gas monitoring, health, marine and environmental research, and food supply chain. III. Summary of the invention

[0006] The present invention aims to provide a new room temperature CO2 sensing material based on amino functionalized MOF material and a preparation method thereof. By amino functionalizing the MIL-In (68) material, controlling the mass ratio of the reactants can have a certain degree of influence on the morphology and gas sensing properties of the product, thereby improving the sensitivity of the sensing material to CO2. The sensing material can achieve high sensitivity and high selectivity CO2 detection under low energy consumption conditions.

[0007] In order to achieve the technical purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0008] 1. Preparation of MIL-68 (In): Weigh hydrated indium nitrate and terephthalic acid, dissolve them in DMF solution, transfer them into a hydrothermal reactor for reaction after ultrasonic treatment, and then obtain the MOFs material MIL-68 (In) through centrifugation, washing and drying.

[0009] 2. Preparation of MIL-68(In)-NH2: Weigh hydrated indium nitrate and 2-aminoterephthalic acid, dissolve them in DMF solution, transfer them into a hydrothermal reactor for reaction after ultrasonic treatment, and then obtain the MOFs material MIL-68(In)-NH2 through centrifugation, washing and drying.

[0010] 3. Amination regulation of MIL-68(In)-NH2: A comparative experiment was carried out using 2-aminoterephthalic acid with a mass gradient of 30mg, 60mg, 90mg, and 120mg to prepare MOFs materials with different degrees of amination to explore the mass ratio with the best sensitivity to CO2.

[0011] 4. Characterization and analysis: Scanning electron microscopy (SEM) was used to observe the microscopic morphology differences between MIL-68(In) and MIL-68(In)-NH2 to determine the effect of amino functionalization on the material morphology. The crystal structure, specific surface area, pore size distribution and chemical composition of the material were characterized in detail by X-ray diffraction (XRD), specific surface area and porosity analysis (BET) and infrared spectroscopy (FT-IR).

[0012] 5. Sensing performance test: Compare the adsorption performance of MOF materials for CO2 before and after amino functionalization, and explore the specific effects of different ratios on CO2 adsorption performance by changing the mass ratio of metal to ligand.

[0013] Preferably, in step 1, 120 mg of hydrated indium nitrate and 120 mg of terephthalic acid are weighed and added to 40 mL of DMF solution.

[0014] Preferably, in step 2, 120 mg of hydrated indium nitrate and 120 mg of 2-aminoterephthalic acid are weighed and added to 40 mL of DMF solution.

[0015] Preferably, in step 3, the masses of 2-aminoterephthalic acid are 30, 60, 90 and 120 mg respectively.

[0016] Preferably, in step 5, an electrochemical workstation It is used for testing to obtain a curve of current variation with time, and data conversion is performed to obtain information of resistance variation with time, thereby obtaining information of CO2 concentration variation.

[0017] Figure 1 The following are SEM images of MIL-68(In) at different magnifications. It can be seen that the crystal morphology of MIL-68(In) material is roughly needle-shaped, with an average size of 10μm.

[0018] Figure 2This is the SEM mapping image of MIL-68(In)-NH2. From the elemental composition of the surface of MIL-68(In)-NH2 material, we can see the presence of four elements: N, C, O, and In, which proves that the amino functionalization of MOF material is successful.

[0019] Figure 3 The SEM images of MIL-68(In)-NH2 at different magnifications are shown below. As the mass ratio of metal to ligand increases, the crystals of the amino-functionalized MOF material become shorter and shorter, but their radius also gradually increases. At the same time, by comparison, it can be seen that the crystal surface of the MIL-68(In) material is smoother than that of the amino-functionalized material, and as the mass ratio increases, the crystal surface of the synthetic material becomes rougher.

[0020] Figure 4 The XRD patterns of MIL-68(In) and MIL-68(In)-NH2 show that MIL-68(In)-NH2 and MIL-68(In) are well crystallized and the crystalline structure of MIL-68(In)-NH2 is comparable to that reported previously, indicating that the MOF material has been successfully amino-functionalized. From the XRD patterns, it can be seen that the amino-functionalized MOFs have a higher crystallinity.

[0021] Figure 5 The infrared spectra of MIL-68(In) and MIL-68(In)-NH2 are shown in Figure 2. In addition to the same characteristic peaks as MIL-68(In), MIL-68(In)-NH2 also has a peak at 3380cm -1 and 3490cm -1 The weak peaks and slightly sharp peaks at 1256 cm-1 and 1267 cm-2 indicate the symmetric and asymmetric stretching vibrations of the amino N–H. The peaks of aromatic amines are located in the low-frequency bands, at 1256 cm-1 and 1267 cm-2, respectively. -1 The stretching vibration of the C–N bond at 1630 cm -1 The bending vibration of the N–H single bond at the peak. The above characteristic peaks confirm the synthesis of MIL-68(In) and a series of MIL-68(In)-NH2 materials with different mass ratios, and also indicate that the amino group has indeed been introduced into the MOFs material. For a series of MIL-68(In)-NH2 with different mass ratios, it can be seen that as the mass ratio increases, the intensity of the amino characteristic peak decreases, indicating that the mass ratio between the metal and the ligand does affect the amount of amino groups carried by the synthesized material, which also corresponds to the aspect ratio shown in the electron microscope image.

[0022] Figure 6This is the XPS spectrum of MIL-68(In)-NH2. The surface elemental composition and chemical state of MIL-68(In)-NH2 were studied, indicating that C, O, N and In elements exist simultaneously in the obtained sample. There are two peaks at 284.9 and 288.9 eV in the C1s region, which are attributed to the sp2 hybridized CC single bond and C=CO bond, respectively. 399.1 eV and 400.8 eV can be seen in the N1s spectrum, which can be attributed to the internal atoms functionalized with the NH group of the skeleton and the terminal CNH amino group. In addition, the 3d XPS spectrum of MIL-68(In)-NH2 can be decomposed into In 3d 3 / 2 and In 3d 5 / 2 These two characteristic peaks reflect the presence of trivalent In.

[0023] Figure 7 The adsorption-desorption isotherms and pore size distribution diagrams of MIL-68(In) and MIL-68(In)-NH2 materials. It can be seen that both materials have characterized IV type curves, proving that both are mesoporous structures. It can also be seen that the main range of pores in MIL-68(In)-NH2-3 material is 4-10nm. At the same time, the specific surface area and pore volume of MIL-68(In)-NH2-3 are 90.6117m 2 / g -1 and 0.0292cm 3 / g -1 The specific surface area and pore volume of MIL-68(In) are 67.2735m 2 / g -1 and 0.0129cm 3 / g -1 The specific surface area and pore volume of the former are larger than those of the latter. Based on the experimental principle, it is preliminarily speculated that the addition of amino groups can also provide more ion binding sites.

[0024] Figure 8This is a test of the sensitivity of MIL-68(In) and MIL-68(In)-NH2 materials to CO2 gas. The highest response point of MIL-68(In) is 1.04, while the highest response point of MIL-68(In)-NH2-3 reaches 1.16, indicating that the gas sensitivity of MIL-68(In)-NH2-3 sensor material far exceeds that of MIL-68(In). Under the same conditions, the highest response points of MIL-68(In)-NH2-4, 3, 2, and 1 sensor materials are 1.138, 1.160, 1.146, and 1.112, respectively. This shows that MIL-68(In)-NH2-3 has the highest sensitivity to CO2 gas, and the gas sensitivity of the amination-modified MOF materials is significantly higher than that of the non-amination-modified MOF materials, proving that amino functionalization is beneficial to improving the gas sensitivity of the sensor material.

[0025] Fig. 9 This is a gas sensing test of MIL-68(In)-NH2 sensing material. The influence of MIL-68(In)-NH2 sensing material on gas sensitivity is different under different environments. The response ability is higher under nitrogen purge than air purge. According to the principle of gas sensing, its sensing performance is different in different atmosphere environments, which means that the sensing material can still directly detect CO2 in an environment without oxygen, proving that the amino mechanism exists for CO2. In a humidity environment of 25%, the highest response point of the sensing material is 1.35, but as the humidity increases, its response ability decreases. In a humidity environment of 75%, the highest response point drops to 1.13. It reflects that the higher the humidity, the lower the sensitivity. It is speculated that the sensitivity of the sensing material is reduced because the H2O molecules occupy part of the pores.

[0026] Fig.10 This is the gas sensitivity test of MIL-68(In)-NH2 sensing material to CO2 in the range of 50-400ppm. It can be found that as the CO2 concentration in the environment increases, the gas sensitivity of the sensing material also increases, indicating that it has a strong response ability. More importantly, even if the CO2 concentration reaches 400ppm, the sensing material still maintains good recovery performance. In the fitting of the CO2 concentration change in the range of 50-400ppm, it can be seen that the sensitivity in the range of 50-400ppm shows a good linear relationship with the CO2 concentration, where r 2 =0.99217, indicating a good fitting relationship, which proves that the material can be used as a potential material for practical applications of carbon dioxide sensors.

[0027] Fig.11This is a schematic diagram of the sensitivity of MIL-68(In)-NH2 sensing material to CO2, CH4, NH3, NO2 and C2H5OH gases. After amination, the sensitivity of the sensing material to the test gas increased, but the response to CO2 increased from 1.06 to 1.38, which was significantly improved. This shows that amination can greatly enhance the gas selectivity of the sensing material to CO2, which may be caused by the increase in the adsorption sites of the sensing material after amino modification.

[0028] Fig.12 This is the cycle stability test and 15-day stability test of the MIL-68(In)-NH2 sensing material. It can be seen that the response / recovery characteristics of the sensing material can be well repeated, and after multiple cycles of 200ppm CO2 gas, the response value has not significantly decayed. At the same time, it can be seen that the sensing material shows good long-term stability. Although the resistance value has decreased, the decrease is gentle and there is no large fluctuation. This shows that the sensitivity is almost not affected, proving that the modification of the amino group does not greatly affect the service life of the sensing material.

[0029] The excellent effects of the present invention are: 1. The present invention significantly improves the adsorption capacity and selectivity of MOF materials for CO2 through amino functionalization, especially showing the best performance in MIL-68(In)-NH2 with a mass ratio of 1:0.75.

[0030] 2. MIL-68(In)-NH2 shows the best CO2 adsorption performance and the highest sensitivity when the mass ratio is 1:0.75. The MOF material at this ratio not only has a higher specific surface area, but also has a pore structure that is more suitable for the adsorption and diffusion of CO2 molecules.

[0031] 3. The preparation process of the MIL-68(In)-NH2 material of the present invention is simple and repeatable, and does not require complicated post-processing, and is suitable for large-scale production and application. IV. Description of the drawings

[0032] Figure 1 This is the SEM image of MIL-68 (In);

[0033] Figure 2 This is the SEM mapping image of MIL-68(In)-NH2;

[0034] Figure 3 It is the SEM image of MIL-68(In)-NH2;

[0035] Figure 4 XRD patterns of MIL-68(In) and MIL-68(In)-NH2;

[0036] Figure 5 The infrared spectra of MIL-68(In) and MIL-68(In)-NH2;

[0037] Figure 6 is the XPS spectrum of MIL-68(In)-NH2;

[0038] Figure 7 The adsorption-desorption isotherms and pore size distribution diagrams of MIL-68(In) and MIL-68(In)-NH2 materials;

[0039] Figure 8 To test the sensitivity of MIL-68(In) and MIL-68(In)-NH2 materials to CO2 gas;

[0040] Fig. 9 Gas sensing test for MIL-68 (In)-NH2 sensing material;

[0041] Fig.10 It is the gas sensitivity test of MIL-68(In)-NH2 sensing material to CO2.

[0042] Fig.11 It is a selective test for MIL-68(In)-NH2 sensing material.

[0043] Fig.12 It is the cyclic stability test and 15-day stability test of MIL-68(In)-NH2 sensing material. V. Specific implementation methods

[0044] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below. The following examples are convenient for better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified.

[0045] Example 1

[0046] A method for preparing a heterojunction sensing material for CO2 gas detection at room temperature, characterized by comprising the following steps:

[0047] (1) Preparation of MIL-68 (In): Weigh 120 mg of hydrated indium nitrate and 120 mg of terephthalic acid, add them to 40 mL of DMF solution, and perform ultrasonic treatment to fully dissolve the hydrated indium nitrate and terephthalic acid. Pour the solution into a 100 mL hydrothermal kettle, adjust the temperature to 120°C, and hydrothermal for 30 minutes. Wash with anhydrous ethanol three times, centrifuge three times, each time for 10 minutes. Finally, filter the solution, collect the precipitate and put it into a vacuum drying oven, set the temperature to 50°C, and dry it for six hours.

[0048] (2) Preparation of MIL-68(In)-NH2: Weigh 120 mg of hydrated indium nitrate and 90 mg of 2-aminoterephthalic acid, add them to 40 mL of DMF solution, and perform ultrasonic treatment to fully dissolve the hydrated indium nitrate and 2-aminoterephthalic acid. Pour the solution into a 100 mL hydrothermal kettle, adjust the temperature to 120°C, and hydrothermal for 30 minutes. Wash with anhydrous ethanol 3 times, centrifuge 3 times, each time for 10 minutes. Finally, filter the solution, collect the precipitate and put it into a vacuum drying oven, set the temperature to 50°C, and dry it for six hours.

[0049] (3) Morphology observation: Scanning electron microscopy (SEM) was used to observe the microscopic morphological differences between MIL-68(In) and MIL-68(In)-NH2 to determine the effect of amino functionalization on the material morphology.

[0050] (4) Structure and performance analysis: The crystal structure, specific surface area, pore size distribution and chemical composition of the material are characterized in detail through techniques such as X-ray diffraction (XRD), specific surface area and porosity analysis (BET) and infrared spectroscopy (FT-IR).

[0051] (5) Performance testing: Compare the CO2 adsorption performance of MOF materials before and after amino functionalization, and explore the specific effects of different ratios on CO2 adsorption performance by changing the mass ratio of metal to ligand.

[0052] Preferred embodiment 1 of the present invention shows the best CO2 adsorption performance and the highest sensitivity under visible light irradiation. The MOF material under this ratio not only has a higher specific surface area, but also its pore structure is more suitable for the adsorption and diffusion of CO2 molecules.

[0053] Example 2

[0054] The other conditions were the same as those in Example 1, except that in step (2), the amount of 2-aminoterephthalic acid added was 30 mg.

[0055] Example 3

[0056] The other conditions were the same as those in Example 1, except that in step (2), the amount of pyrrole added was 60 mg.

[0057] Example 4

[0058] The other conditions were the same as those in Example 1, except that in step (2), the amount of pyrrole added was 120 mg.

Claims

1. A CO2 room temperature sensing material based on amino functional MOF material, characterized in that MIL-68(In)-NH2 is used as the sensitive material. The morphology of the product is regulated by controlling the mass ratio of the reactants. As the aspect ratio changes, the degree of attachment of the amino group also changes, which has a certain degree of influence on the gas sensing performance.

2. According to claim 1, two MOFs materials, MIL-68(In) and MIL-68(In)-NH2, were synthesized at 120°C by hydrothermal method.

3. According to claim 2, wherein MIL-68(In) is synthesized by a hydrothermal method at 120°C by adding hydrated indium nitrate and terephthalic acid into a DMF solution.

4. According to claim 2, wherein MIL-68(In)-NH2 is synthesized by hydrothermal method at 120°C by adding hydrated indium nitrate and 2-aminoterephthalic acid into DMF solution.

5. According to claim 4, MIL-68(In)-NH2 with different degrees of amination is obtained by adjusting the quality of 2-aminoterephthalic acid.

6. According to claim 4, the CO2 detection performance is optimized by adjusting the degree of amination.

7. A method for preparing a CO2 room temperature sensing material according to the above claim, characterized in that The degree of amination of MIL-68(In)-NH2 was adjusted to optimize the CO2 adsorption performance and response characteristics of the sensing material.